PECULIARITIES OF FORMATION INFORMATION-ACCUMULATED (BIG DATA) MODELS OF THE CITY - , С. М. (Municipal economy of cities. Series: «Economy science», 2018)
The article outlines the principles of building an information-accumulative model for analyzing the function and development of a city. The model allows to reveal the hierarchical system of processes of its vital activity and to estimate the degree of their influence on the city as an open dynamic system. This in turn makes it possible to determine the urgency and importance of making the necessary decisions, to avoid a number of systemic mistakes and to forecast the directions of the city's life, potentially dangerous for its stable existence. As a result, we get a model that can track and manage complex information flows, analyze them and combine data according to predefined parameters. In addition, thanks to the feedback that has appeared, the model is a tool for forecasting and approbation of changes made to the city. This allows you to determine the urgency and significance of decisions, allows you to predict, and thus avoid a number of system errors that can be critical in influencing the situation in the city. Keywords: information, city, development, model, prognostication, system.